Meeting the online educational needs of international health promoters: an evaluation of a comprehensive, multilingual global training program in tobacco control. (June 2016) - Spires, Mark; Cohen, Joanna
Introduction: An evaluation of a global online training program in tobacco control offered in multiple languages was conducted to identify ways in which the varied online educational needs of its international participants could be more effectively met. Methods: An online survey was administered to a sample of training participants to solicit feedback regarding course content and delivery. In addition, participants' training site usage patterns were examined. Results: Findings showed high levels of satisfaction with training content and delivery, as well as of knowledge acquisition and utilization. Respondents indicated that it was important that course content be current and relevant to their practice. Conclusions: Although findings are consistent with best practices for online continuing education, in practice it is challenging to keep material updated, incorporate examples and case studies from the participants' countries, and integrate adequate opportunities for interactivity when a course has geographically and linguistically diverse participants. Low-cost, technologically appropriate solutions should be developed to maximize the effectiveness of similar continuing education programs for health promoters worldwide.